Nucleoside-Lipid-Based Nanocarriers for Sorafenib Delivery - Benizri, Sebastien (Nanoscale Res Lett, 2018)
Although the application of sorafenib, a small inhibitor of tyrosine protein kinases, to cancer treatments remains a worldwide option in chemotherapy, novel strategies are needed to address the low water solubility (< 5 μM), toxicity, and side effects issues of this drug. In this context, the use of nanocarriers is currently investigated in order to overcome these drawbacks. In this contribution, we report a new type of sorafenib-based nanoparticles stabilized by hybrid nucleoside-lipids. The solid lipid nanoparticles (SLNs) showed negative or positive zeta potential values depending on the nucleoside-lipid charge. Transmission electron microscopy of sorafenib-loaded SLNs revealed parallelepiped nanoparticles of about 200 nm. Biological studies achieved on four different cell lines, including liver and breast cancers, revealed enhanced anticancer activities of Sorafenib-based SLNs compared to the free drug. Importantly, contrast phase microscopy images recorded after incubation of cancer cells in the presence of SLNs at high concentration in sorafenib (> 80 μM) revealed a total cancer cell death in all cases. These results highlight the potential of nucleoside-lipid-based SLNs as drug delivery systems. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s11671-017-2420-2) contains supplementary material, which is available to authorized users.